Genetic variability in castor (Ricinus communis L.): Genetic variability in castor (Ricinus communis L.) - PATEL ANKIT; C J PATEL; D K PATEL (Journal of Oilseeds Research, 2020)
A set of 60 castor genotypes was evaluated for assessment of genetic variability, heritability and genetic advancepercent mean with respect to nine characters. The GCV and PCV were the highest for number of capsules on primary raceme followed by seed yield per plant, number of branches per plant and plant height. High genetic variability coupled with high heritability and high genetic advance was recorded for all the traits except days to flowering, days to maturity, number of nodes/plant, and oil content (%) indicating that direct selection for these traits could be effective.